Effect of mechanical damage in soybean seeds on seedling growth and final seed yield - Chin, Hoong Fong; Neales, T. F.; Wilson, J. H. (Faculty of Agriculture, University of Malaya, 1974)
Mechanical damage to seed is hard to detect except with X-rays. Seed damage rras adverse effects on growth and development of soybean (Glycine max L.J plants. This is manifested in reduction in dry weight of seedlings and final seed yield as high as 25% and 45% respectively. But the percentage germination is not affected in freshlv harvested seeds. In spite of reduced seedling size, it is surprising to note that net assimilation rate and relative growth rate tend to be higher in plants grown from damaged seeds